Process and reliability of die attachment by time-reduced sintering of nanosilver film - Dai, Jingru (2019)
This study focused on the time-reduced sintering process of nanosilver film and power cycling reliability of the sintered die attachments. The aim is to demonstrate whether the time-reduced sintered joints formed within seconds have sufficient strength to survive the subsequent assembly processes such as wire bonding and whether the reliability of the time-reduced sintered joints is still better or at least comparable to that of the high lead solder joints without losing the competitiveness on the processing time. The sintered joints were prepared by commercial available nanosilver dry film and a recently developed high accuracy die bonder. The whole process for each die attachment takes only a few seconds and the sintering time is reduced to less than 9 s. The sintering behaviour of nanosilver film was studied by uniform design-of- experiments for considering three critical sintering parameters. Analysis of the sintered joints was conducted by die shear strength test and porosity measurement. Results of parametric study show that use of nanosilver dry film together with a die bonder for accurate control over sintering parameters can produce high strength, reproducible sintered joints within seconds of sintering time. At the same time, the relationship between these sintering parameters and the shear strength and porosity/density has been established and processing windows for time-reduced sintering processes at different manufacturability conditions have been drawn. The power cycling reliability of the sintered die attachment for attaching SiC diodes was carried out and compared with Pb5Sn soldered die attachment by using constant temperature swing of 50 to 200 ºC. The thermal performance and microstructure evolution of the sintered die attachments were characterized regularly and correlated with each other. The results showed that the sintered joints formed by time-reduced sintering processes demonstrated a similar power cycling reliability when the bonding strength varied from 20.5 to 40.5 MPa or the porosity changed from 35.5 to 50.9 %. Their thermal effective conductivity decreased nearly linearly from ~100 to ~13 W/(m2·K) as the power cycling test proceeded from zero to ~600k power cycles. On the other hand, the sintered die attachment with a higher bonding strength (~52.7 MPa)/low porosity (~24.7 %) could maintain its effective thermal conductivity of ~100.9 W/(m2·K) nearly unchanged up to ~100k power cycles. By contrast, the effective thermal conductivity of Pb5Sn degraded rather rapidly from 43.7 to 12.5 W/(m2·K) as the power cycling test proceeded from zero to 60k power cycles. All the thermal performance results can be well correlated with the evolution of their microstructures during power cycling.